The Influence of Music on the Communication and Social Skills of Learners With Autism (International Journal of Scientific Research and Management (IJSRM), 2025)
This study examined the influence of music on the communication and social skills of learners with autism at Mandaue City Central SPED School, Mandaue City SPED High School, and Basak Elementary School during the Academic Year 2021–2022, serving as the basis for a proposed Communication and Social Skills Enhancement Plan. Utilizing a descriptive-correlational method, the study gathered data through questionnaires administered to parent and teacher respondents using a universal sampling technique. Data were analyzed using percentages, total weighted points, weighted mean, t-test, and Pearson product-moment correlation. Results showed that music was perceived to have a high influence on communication and social skills by parents, and a very high influence by teachers. Parents also rated learners’ communication and social skills as high. A significant difference was found between parents’ and teachers’ perceptions regarding music’s influence on these skills. While there was no significant relationship between parents’ perception and learners’ communication skills, a significant relationship existed between parents’ perception and learners’ social skills. Based on the findings, it was concluded that music significantly contributes to enhancing the communication and social skills of learners with autism. Therefore, the adoption of a Communication and Social Skills Enhancement Plan is strongly recommended.